2012
DOI: 10.1097/aog.0b013e31825f269f
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Umbilical Cord Clamping in Premature Neonates

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 21 publications
1
38
0
6
Order By: Relevance
“…This protection from RBC transfusions is present up to 6 weeks of life, and serum iron ferritin levels remain increased as well. 16,20,24,25 Of the most significant impacts on perinatal morbidity and mortality is the decreased incidence of intraventricular hemorrhage (IVH) with delayed cord clamping.…”
Section: Benefitsmentioning
confidence: 99%
“…This protection from RBC transfusions is present up to 6 weeks of life, and serum iron ferritin levels remain increased as well. 16,20,24,25 Of the most significant impacts on perinatal morbidity and mortality is the decreased incidence of intraventricular hemorrhage (IVH) with delayed cord clamping.…”
Section: Benefitsmentioning
confidence: 99%
“…Studies have shown that low birth weight infants undergoing DCC are warmer than those undergoing ICC, possibly because of the warm placental blood entering the newborn. 17 UCM allows rapid placement of the newborn under the radiant warmer. The admission temperatures were not different between groups.…”
Section: Figurementioning
confidence: 99%
“…No obstante, en un estudio reciente, Kaempf et al 38 aportaron interesantes resultados al comparar la evolución clínica de 77 prematuros de muy bajo peso al nacer (MBPN) y 172 con bajo peso al nacer (BPN). Todos tenían menos de 35 semanas y el clampeo fue demorado hasta los 45 segundos versus un número igual de controles históricos nacidos durante el período inmediatamente anterior, cuando se practicaba el clampeo temprano.…”
Section: El Aporte De Hierro Durante La Transfusión Placentariaunclassified